2019
DOI: 10.1152/ajpheart.00597.2018
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune response in the pathogenesis of heart failure in survivors of myocardial infarction

Abstract: Among the different cardiovascular disease complications, atherosclerosis-induced myocardial infarction (MI) is the major contributor of heart failure (HF) and loss of life. This review presents short- and long-term features of post-MI in human hearts and animal models. It is known that the heart does not regenerate, and thus loss of cardiac cells after an MI event is permanent. In survivors of a heart attack, multiple neurohumoral adjustments as well as simultaneous remodeling in both infarcted and noninfarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 144 publications
(185 reference statements)
1
16
0
Order By: Relevance
“…The gene changes within the blue module were strongly induced on the first day of AMI, upon admission to the health care facility. These results suggested that the extent of myocardial damage during the acute phase is closely associated with the stable heart function progressing into HF (Epelman et al, 2015; Zimmer et al, 2019). The identified transcripts present during the first day of AMI can serve as a tool contributing to early diagnosis of the development of HF after AMI.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The gene changes within the blue module were strongly induced on the first day of AMI, upon admission to the health care facility. These results suggested that the extent of myocardial damage during the acute phase is closely associated with the stable heart function progressing into HF (Epelman et al, 2015; Zimmer et al, 2019). The identified transcripts present during the first day of AMI can serve as a tool contributing to early diagnosis of the development of HF after AMI.…”
Section: Discussionmentioning
confidence: 88%
“…Their results provided deep insights into the critical roles of lncRNAs in the pathology of HF. However, the genes identified by Pang et al came from patients with HF including ischemic and non-ischemic causes, which have been shown to be heterogeneous in terms of clinical presentation and prognosis (Zimmer et al, 2019). Our study identified the key genes in HF post-AMI, and determined the role the key genes as early prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a). Although we are not the first to demonstrate the hyperactive inflammatory responses of immune cells to either cDAMP or LPS during CCS (Laukova M et al, 2018;Zimmer A et al, 2019), we are to first to profile and compare the two to show the similarity in their proinflammatory and anti-inflammatory cytokine expressions (Fig. 2b).…”
Section: Discussionmentioning
confidence: 99%
“…The adult mammalian heart is among the least regenerative organs thus cardiomyocytes (CMs) are threatened by a multitude of factors; such as necrosis, apoptosis, and oncosis (or ischemic cell death), which may lead to heart failure [1, 2]. Necrosis, or premature cell death due to physical or chemical injury, and apoptosis, or programmed cell death, have more recently been found to be linked together during pathological states of heart disease [3]. Regarding cardiac pathogenesis, myocardial infarction results in scar tissue, regions where CMs are replaced with fibrillar collagen and/or fibroblast-like cells [4].…”
Section: Introductionmentioning
confidence: 99%